You can treat x and 2x+1 just as though they are real numbers.
So f(2x+1) = 3(2x+1) - 5 = 6x + 3 - 5 = 6x - 2
In the above, I made use of something called the distributive law which says that if a,b and c are real numbers, then a(b+c) = ab + ac.
The answer is A!
Sadie is correct because 3(2x+3y) equals 6x+9y
Answer:
12a + .5B
B= -6a
a=.042B
Step-by-step explanation:
1/2(6a+B)= 12a+.5B
1/2(6a+B)=0
-12a=.5B
-6a=B
12a=-.5B
a=.042B
Answer:
-180√3
Step-by-step explanation:
3√10 x - 6√30
= 3x-6 x -√10 x √30
= -18 x√300
= -18 x 10√3
= -180√3
Answer:
n=−3
Step-by-step explanation: